Noncoding RNAs in pyroptosis and cancer progression: Effect, mechanism, and clinical application - Zhang, Menghui; Dang, Pengyuan; Liu, Yang; Qiao, Bingbing; Sun, Zhenqiang (Frontiers in Immunology, 2022)
Pyroptosis, an inflammatory form of programmed cell death (PCD), causes inflammation in cells. The influence of pyroptosis on tumour is complicated. On the one hand, Pyroptosis triggers antitumour response. On the other hand, pyroptosis may induce carcinogenesis. Pyroptosis is regulated by various factors, especially non-coding RNAs. In this review, we discuss the effects of ncRNAs on pyroptosis and the mechanisms by which ncRNAs regulate pyroptosis. Besides, we introduce the influence of ncRNA on tumour resistance via pyroptosis. Additionally, we summarize how ncRNA-associated pyroptosis modulates tumour microenvironment (TME) and thereafter triggers antitumour immune response. Finally, pyroptosis-related ncRNAs may act as biomarkers and therapeutic targets clinically.